Exploring the relationship between development aid and FDI from developed countries in developing countries: empirical insights from Japanese firm-level data - Bertrand, Olivier; Betschinger, Marie-Ann (Journal of International Business Studies, 2024)
Development aid is recognized in the fields of international relations and development economics as an important geopolitical tool for supporting the outward FDI of developed countries in developing countries. However, little attention has been given to the role of firm heterogeneity, a central concept in IB, in the aid–FDI relationship. This study helps address this gap by bringing the aid–FDI nexus to the level of the firm. We argue that both infrastructure and non-infrastructure aid encourage private home firms’ FDI entries, even when unrelated to aid project execution. We propose that developed-country firms that are less able to manage host-country challenges or have access to the home state should be more sensitive to both types of aid. Analyzing data from 1451 private Japanese firms in 76 developing countries (1991–2002), we find that both types of aid raise the FDI entry likelihood. However, the firm-level contingencies are confirmed only for the infrastructure aid–FDI nexus. Non-infrastructure aid seems to mitigate market and political uncertainties that home firms are less capable of tackling on their own. This study complements research in IB that focuses on Chinese infrastructure aid and emphasizes infrastructure-related FDI and political expansion motives of SOEs in the aid–FDI nexus.